Allelopathic Proclivities of Azadirachta indica on Agricultural Crops - Divya, M.P.; Yassin, M. Mohamed (Indian Journal of Agroforestry, 2020)
The allelopathic effect of Azadirachta indica on agricultural crops was tested with four soil media viz., top soil, rhizosphere soil and field soil mulched with dry leaves of three-year-old Azadirachta indica and ordinary field soil as control. When compared to the ordinary field soil, the reduction in the growth and yield of four test crops viz., cowpea, sesame, horsegram and sorghum was observed with the neem associated soil media. The results revealed that maximum reduction in germination was recorded with top soil. The maximum reduction in shoot length, root length at harvest and grain yield was recorded with rhizosphere soil. The highest reduction in the drymatter production at harvest was recorded with soil mulched with dry leaves. It was found that Azadirachta indica was having allelopathic effect on annuals.Â